F response and somatosensory and brainstem auditory evoked potential studies in HMSN type I and II. Issue 11 (November 1992) - Scaioli, V; Pareyson, D; Avanzini, G; Sghirlanzoni, A
Abstract : To evaluate conduction along the proximal and distal segments of motor and sensory long limb nerves, as well as along the very short acoustic nerve, F response and somatosensory and brainstem auditory evoked potential were studied in a series of patients with hereditary motor and sensory neuropathy (HMSN) types I and II. A diffuse and comparable slowing of conduction in proximal and distal nerve segments, as well as along the acoustic nerve, seems to favour a primary myelin defect in HMSN I. F response and motor conduction velocity showed a similar derangement in both proximal and distal motor segments. Latencies of somatosensory evoked potentials were symmetrically prolonged and correlated with motor nerve impairment. Central conduction times were normal. Studies of brainstem auditory evoked potentials showed a high incidence of acoustic nerve involvement, the most evident abnormality being a statistically significant increase in the latency of the I wave. Our data seem to support the presence of primary myelinopathic damage in HMSN I.